2004
DOI: 10.2209/tdcpublication.45.47
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Phagocytic Role of Surface Fibrous Structure of an Invasive Porphyromonas Gingivalis Strain

Abstract: Recent studies have shown that invasive and non-invasive strains of Porphyromonas gingivalis can both be isolated from patients with periodontitis. We examined the interaction between an invasive 16-1 P. gingivalis strain and phagocytes obtained from human peripheral blood and guinea pig peritoneal cavity. Phagocytes from human peripheral blood, mainly polymorphonuclear leukocytes (PMNs) isolated by centrifugation in Ficoll Hypaque, and macrophages collected from the peritoneal cavity of guinea pigs, were expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Because of its many virulence factors, such as proteases, P. gingivalis can modulate host cytokine signaling networks and generate inflammatory infiltrates that are responsible for the chronic nature of periodontitis. Previous studies have shown that P. gingivalis can survive, spread to neighboring host epithelial cells, and resist phagocytosis in vitro (Cutler et al ., ; Miyabe et al ., ). In vivo , P. gingivalis has been identified in pathological gingiva using several methods, including immunofluorescence, immunohistochemistry, and fluorescence in situ hybridization (Rudney et al ., ; Kim et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Because of its many virulence factors, such as proteases, P. gingivalis can modulate host cytokine signaling networks and generate inflammatory infiltrates that are responsible for the chronic nature of periodontitis. Previous studies have shown that P. gingivalis can survive, spread to neighboring host epithelial cells, and resist phagocytosis in vitro (Cutler et al ., ; Miyabe et al ., ). In vivo , P. gingivalis has been identified in pathological gingiva using several methods, including immunofluorescence, immunohistochemistry, and fluorescence in situ hybridization (Rudney et al ., ; Kim et al ., ).…”
Section: Introductionmentioning
confidence: 97%